2018
DOI: 10.1186/s13063-018-2864-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research on the efficacy and safety of thread-embedding acupuncture for treatment of herniated intervertebral disc of the lumbar spine: a protocol for a multicenter, randomized, patient–assessor blinded, controlled, parallel, clinical trial

Abstract: BackgroundA lumbar herniated intervertebral disc (LHIVD) is a common problem that usually causes lower back pain and neurological symptoms that manifest as radiating pain. Several studies have reported that thread-embedding acupuncture (TEA) is effective in the treatment of LHIVD. However, these studies were of low quality and there is therefore little clinical evidence for the effectiveness of TEA in this regard. The aim of the present study is to establish the clinical evidence regarding the efficacy and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the embedded thread, which is gradually absorbed into the body, causes a long-term therapeutic effect through mechanical and chemical stimulation at the treatment site. 26 In this trial, a STEA needle without the thread will be set as the control intervention, with reference to previous studies 22,27,28 to confirm only the effect of the embedded thread, excluding the stimulation effect of needle insertion. Additionally, to confirm the long-term maintenance effect, 8 weeks of follow-up assessment will be conducted after the end of treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the embedded thread, which is gradually absorbed into the body, causes a long-term therapeutic effect through mechanical and chemical stimulation at the treatment site. 26 In this trial, a STEA needle without the thread will be set as the control intervention, with reference to previous studies 22,27,28 to confirm only the effect of the embedded thread, excluding the stimulation effect of needle insertion. Additionally, to confirm the long-term maintenance effect, 8 weeks of follow-up assessment will be conducted after the end of treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…This RCT had approval from the Institutional Review Boards of the institutions involved (KHUHGD: KHNMCOH 2016-09-006, KHUMC: 161216-HR-006, DUBOH: 2016-0012, DKMHDHU: DHUMC-D16015-PRO-02) [12].…”
Section: Analysis Designmentioning
confidence: 99%
“…In the RCT [12], participants were selected by the following criteria; (1) men or women aged 19 to 70 years; (2) patients whose magnetic resonance image or computed tomography image showed a severe bulging abnormality in the lumbar spine and corresponding symptoms of radiating pain; (3) patients who complained of low back pain and indicated more than 40 mm on the 100 mm VAS; and (4) patients who voluntarily participated and agreed to give signed informed consent, after hearing the details of the clinical trial.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations